2012
DOI: 10.1002/pmic.201200151
|View full text |Cite
|
Sign up to set email alerts
|

MS‐based ligand binding assays with speed, sensitivity, and specificity

Abstract: Immunoassays are widely used in biochemical/clinical laboratories owing to their simplicity, speed, and sensitivity. We combined self-assembled monolayer-based immunoassays with MALDI-TOF MS to show that high-fidelity surface preparations with a novel matrix deposition/crystallization technique permits quantitative analysis of monolayer-bound antigens at picomolar detection limits. Calibration curves for intact proteins are possible over a broad concentration range and improved specificity of MS-immunoassays i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Plus, while the observed linear dynamic range is in general agreement with the reported ∼4000 dynamic range of our instrument; it is important to note that, under max injection time conditions, the intensity data is extrapolated from known equations in order to arrive at quantitative trends similar to that of a triple quadrupole mass spectrometer. 54,34 Overall, the work highlights baseline figures of merits associated with the IEF-SPLC-FTMS workflow that could be improved upon in diverse ways. For example, future investigations should continue to explore protein pI, size, amount, and PTM pK a impacts on the detection of distinct modification clases (e.g., citrullination which are early indicators of neurodegenerative diseases 55−57 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plus, while the observed linear dynamic range is in general agreement with the reported ∼4000 dynamic range of our instrument; it is important to note that, under max injection time conditions, the intensity data is extrapolated from known equations in order to arrive at quantitative trends similar to that of a triple quadrupole mass spectrometer. 54,34 Overall, the work highlights baseline figures of merits associated with the IEF-SPLC-FTMS workflow that could be improved upon in diverse ways. For example, future investigations should continue to explore protein pI, size, amount, and PTM pK a impacts on the detection of distinct modification clases (e.g., citrullination which are early indicators of neurodegenerative diseases 55−57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before axis normalization ∼95% of observed proteoforms exhibited an inter-replicate RT precision from the mean of ±30 s. This reduced to ±12 s after normalization of the RT axis (Figure 3D), which is consistent with RT reproducibility previously shown for 1D SPLC-FTMS. 34 The observed w pI precision from the inter-replicate mean was ±0.33 prior to axis normalization, which reduced to ±0.21 after (Figure 3E). However, further evaluation revealed that the precision estimate was generally independent of species mass but dependent on intensity (Figure S4).…”
Section: Benchmark Ief-splc-ftms Figures Of Merit For Amentioning
confidence: 93%
See 1 more Smart Citation
“…TLT/VIC was performed as previously described. 10,11 MALDI matrix, α-cyano-4hydroxycinnamic acid (CHCA), was sublimed at ∼25 ng/mm 2 surface density and VIC performed with methanol. Samples were analyzed with a Voyager DE-Pro MALDI-TOF MS (Applied Biosystems, Inc., Foster City, CA).…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…The combination of controlled analyte density on the surface with homogeneous matrix/analyte cocrystallization by TLT/VIC enabled assay precisions similar to those observed for photometric immunoassays and supports label-free quantitation via end-point calibration curves. 10 The previous work also demonstrated quantitative detection of analyte from complex matrices including biofluids. Additionally, combining enrichment of target analyte with antibodies and MALDI-TOF yields key molecular mass information, providing a high degree of assay selectivity for resolving related or complexed species.…”
Section: ■ Introductionmentioning
confidence: 98%